Comparison of tentative radiographic working length with and without grid versus electronic apex locator - Tanikonda Rambabu; Visinigiri Srikanth; Girija S Sajjan; Sirisha Ganguru; Chava Gayatri; K Roja (Wolters Kluwer Medknow Publications, 2018)
The apical termination of obturation is the most important factor influencing the success of root canal treatment (RCT). Working length (WL) is the key element in achieving this. Aim: The aim of this study is to compare and evaluate the preoperative estimated WL with conventional radiograph and with grid radiograph, with reference to electronic apex locator (EAL) in single-rooted teeth. Settings and Design: Thirty permanent anterior teeth with complete root formation indicated for RCT were included in this study. Materials and Methods: Conventional radiograph (Group 1) and conventional radiograph with external grid (Group 2) were made before access opening. WL with EAL (Group 3) was determined after access opening. Statistical Analysis: The statistical package for the social sciences (SPSS) version 16.0 (SPSS Inc., Chicago, IL, USA) was used to compare the WLs of three groups, and the statistical significance was considered to be P ≤ 0.05. ANOVA, post hoc test were made to measure the intergroup comparison, and Pearson correlation values were obtained. Results and Conclusion: The results of the study showed a higher correlation between grid WL and apex locator WL than conventional WL and apex locator WL. Preoperative metrics with radiographic grid along with the apex locator is a better measuring tool compared to the conventional radiographic WL in a single-rooted tooth.